2018
DOI: 10.1038/s41598-018-27141-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of CCR7+CD8+ T cells in kidney transplant recipients with allograft rejection

Abstract: The regulatory function of CCR7+CD8+ T cells against effector T-cells involved in T-cell mediated rejection (TCMR) in kidney transplant recipients was investigated. In vitro experiments explored the ability of CCR7+CD8+ T cells to suppress T-cell proliferation under T-cell activation conditions or during coculture with human renal proximal tubular epithelial cells (HRPTEpiC). In an ex vivo experiment, the proportion of CCR7+/CD8+, FOXP3+/CCR7+CD8+ T and effector T-cell subsets were compared between the normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…Recently, several investigators have been studying the biological effects of plasma‐activated media (PAM) or plasma activated water (PAW) and the chemistry of liquid‐plasma interactions . In addition, it has been reported that cancer cells are more susceptible to plasma treatment than normal cells and reactive oxygen species (ROS) stress induces death mainly through apoptosis …”
Section: Introductionmentioning
confidence: 99%
“…Recently, several investigators have been studying the biological effects of plasma‐activated media (PAM) or plasma activated water (PAW) and the chemistry of liquid‐plasma interactions . In addition, it has been reported that cancer cells are more susceptible to plasma treatment than normal cells and reactive oxygen species (ROS) stress induces death mainly through apoptosis …”
Section: Introductionmentioning
confidence: 99%
“…ROS and RNS are known to induce cell proliferation as well as cell death. ROS are known to induce both apoptosis and necrosis, while RNS can induce cell death via damage DNA . Our results in Figure show that the ROS concentration is highest at 20‐min treatment while the RNS concentration is highest at 30 min.…”
Section: Resultsmentioning
confidence: 56%
“…The Harsh PAM (Figure C and F) led to the total loss of cluster organization and to single cells with quasi‐spherical shape due to cells de‐adhesion, much more evident for the SAOS‐2 cells attesting for a more sensitivity of cancer cells to environmental changes. Such morphological changes were probably due to the PAM‐mediated disruption of adhesive proteins, membrane receptors, and fibronectin in cancer cells …”
Section: Resultsmentioning
confidence: 99%